Researching scientometrically the backgrounds on medical education: 19th century French doctoral theses. - Fernández-Guerrero, Inés M.; Fernández-Cano, Antonio (Spanish Journal of Medical Education, 2026)
Introduction. This study conducts a scientometric and historiographic review of doctoral theses on medical education defended at French universities throughout the 19th century in search of the antecedents of this multidisciplinary field. Method. Quantitative (scientometric) review study with intentional sampling. Twenty-eight bibliographic records of these theses were retrieved ad hoc from the French databases SUDOC (Système Universitaire de DOCumentation) and bnf (Bibliothèque Nationale de France). Results. Scientometric patterns are provided for: longitudinal production as a 6th-order polynomial function; institutional productivity with five French universities, of which Paris is the most productive; and production by gender with three theses defended by women (11% of the total). The diversity of thematic areas inferred confirms the multidisciplinary and interdisciplinary nature of medical education since its origins, which can be dichotomized into medical and non-medical disciplines. The textual analysis reveals the plurality of terms inferred from the titles to configure a final network analysis consisting of a central cluster of 25 theses and three peripheral ones. Discussion. It can be said that French doctoral thesis production during the 19th century was abundant, varied, and showed clear scientometric patterns, which denotes the relevance of French medical education as the historical research vanguard of this multidisciplinary field.